(untitled) (Revista Música, 2023)
The main aim of this paper is to analyse the levels of music performance anxiety among the participants of an academic choir within the degree programme in Music Education of the Superior School of Education, Polytechnical Institute of Porto. The academic literature demonstrates a scarcity of studies that investigate music performance anxiety among singers, and in particular, among choral singers. Furthermore, academic choirs have received little attention in academic literature, in similarity with other choral singing practices in Portugal. A case study of the choir of the Superior School of Education, Polytechnical Institute of Porto involved the collection of socio-demographic data in order to characterise the choir members. The State-Trait Anxiety Inventory (STAI) was applied in two distinct moments, in order to measure the levels of state anxiety and trait anxiety. The results of the STAI correlate with previous studies in terms of the links between anxiety and gender, while other factors, such as performing solo, did not have a statistically significant impact on the participants. Meanwhile, the socio-demographic questionnaire demonstrates the heterogenous nature of the students on the Music Education degree programme at the Superior School of Education, Polytechnical Institute of Porto, principally in terms of age and performance practice.